Glacial Oscillations and Climate Variability in the NE Greenland - Garcia-Oteyza Cira, Julia (Universitat de Barcelona, 2024)
Programa de Doctorat en Geografia, Planificació Territorial i Gestió Ambiental [eng] The remote coastal ice-free areas of Northeast Greenland National Park are considered a unique laboratory to examine the chronology of past cold-climate geomorphological processes and associated climatic conditions. This dissertation endeavors to employ a multidisciplinary approach, leveraging various natural archives and employing complementary techniques. The overarching goal is to enhance our understanding of the glacial history and climate variability within the specified region. Four valley environmental reconstructions are presented here, combining geomorphological mapping and a geochronological dataset of 84 10Be cosmogenic radionuclide exposure (CRE) dating samples (in some cases complemented with OSL dating and historical data) to reconstruct glacial oscillations. In addition, a multiproxy characterization of lake sediment records is provided, using seven different but complementary paleolimnological methods together with 13 14C dating, to unravel climate variability of the last millennia, with a focus on local temperature and precipitation regimes. The highest CRE-dated samples indicate that these valleys were fully glaciated before the global Last Glacial Maximum (LGM) at ~80-50 ka. After the LGM, a rapid deglaciation process with massive ice thinning occurred, and most of the currently ice-free areas of the region were deglaciated at the end of Termination-1. The complete sequence of moraine ridges distributed across the slopes surrounding the Zackenberg Valley floor revealed ice thinning between ~13.7 and 11.2 ka, followed by accelerated glacier retreat at ~10-11 ka, when the valley glaciers disconnected from the main ice tongues. Deglaciation of the fjord entrance valleys and terminal valleys occurred during the Early Holocene at ~10-8.5 ka, due to the long-term decrease of precipitation. This long-term recession was interrupted by periods of glacial stillstand/ advance of the valley glaciers that favored the ...